Pseudomonas aeruginosa adapts its iron uptake strategies in function of the type of infections - Cornelis, Pierre; Dingemans, Jozef (Frontiers in Cellular and Infection Microbiology, 2013)
Pseudomonas aeruginosa is a Gram-negative γ-Proteobacterium which is known for its capacity to colonize various niches, including some invertebrate and vertebrate hosts, making it one of the most frequent bacteria causing opportunistic infections. P. aeruginosa is able to cause acute as well as chronic infections and it uses different colonization and virulence factors to do so. Infections range from septicemia, urinary infections, burn wound colonization, and chronic colonization of the lungs of cystic fibrosis patients. Like the vast majority of organisms, P. aeruginosa needs iron to sustain growth. P. aeruginosa utilizes different strategies to take up iron, depending on the type of infection it causes. Two siderophores are produced by this bacterium, pyoverdine and pyochelin, characterized by high and low affinities for iron respectively. P. aeruginosa is also able to utilize different siderophores from other microorganisms (siderophore piracy). It can also take up heme from hemoproteins via two different systems. Under microaerobic or anaerobic conditions, P. aeruginosa is also able to take up ferrous iron via its Feo system using redox-cycling phenazines. Depending on the type of infection, P. aeruginosa can therefore adapt by switching from one iron uptake system to another as we will describe in this short review.